The Uniqueness Of Kayie Dance Art In Village Laban Nagari Salido District IV Jurai Painan South Pesisir Based On Space, Time, And Energy Aspects - Nilam Permata Sari; Budiwirman Budiwirman (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
The traditional art of Kayie Dance in Laban Nagari Salido Village, IV Jurai Painan District, the South Pesisir is an identity for the life of the community itself, because this art reflects the activities of the South Coast community who work as fishermen. As a source of livelihood and fishing activities in the southern coastal area, the community believes in the value of life that comes from catching fish in the sea or river. Moving away from the values ​​of life, local artists have created art that is characteristic of the southern coastal area, especially in the village of Laban Nagari Salido, District IV Jurai Painan. The uniqueness of this art is that it combines beautiful and rhythmic movements, and each movement has its own beautiful value. The Kayie dance has its own uniqueness which is created by the dance atmosphere expressed through the dance movements. Kayie's dance has 11 main movements in the dance, starting with the initial sambah movement to the closing sambah movement. There are many aspects of beauty contained in every element of the Kayie Dance art. The function of the Kayie Dance is as a means of entertainment and learning for all levels of society, this is an attraction for the community to preserve the Kayie dance on the South Pesisir.